Comparing the military presence and strength of the United States of America and the Russian Federation in the Mediterranean Region in the 21st century - Ψάλτης, Σωκράτης (Πανεπιστήμιο Πελοποννήσου, 2019)
Historically, the Mediterranean Sea, and particularly its Eastern part was considered strategically important since the antiquity, an importance confirmed in recent times by both theoreticians of history and international relations as well as great power politics. Today the importance of the region remains, as it connects sea routes with from the Black Sea and the Atlantic to the Suez Canal and the Indian Ocean. Simultaneously regional and great powers have to face contemporary challenges like migration, Islamic radicalism and terrorism. Since the Cold War, USA and (formerly the Soviet Union and now) Russia are politically and militarily involved in the region each trying to achieve its political and military objectives which are often clashing. Through these years, the US alone or within a system of regional or wider alliances has managed to maintain the military and political advantage. But, Russia is making gains in recent years particularly through establishing a firm military presence in key regional points such as Syria. As other actors, like China, are gradually entering this stage, the contest and its future outcome remains an open-ended process.
Keywords: Ηνωμένες Πολιτείες Αμερικής--Εξωτερικές σχέσεις; Ρωσία--Εξωτερικές σχέσεις; Στρατιωτική πολιτική; Μεσόγειος, Περιοχή της; Μεσόγειος; Ηνωμένες Πολιτείες Αμερικής; Ρωσία; ΝΑΤΟ; Συρία